Hybridization of Ficus religiosa with F. septica and F. aurea (Moraceae) - Ramírez B, William (Universidad de Costa Rica, 1994)
There is strong evidence that the agaonid wasps (Agaonidae) are very specific 10 their fig hosts (Wiebes 1963, 1986, Hill 1967, Ramírez 1971). Introduced species normally fail 10 set viable seeds when tbeir own wasps are absent (Ramírez 1971, Rarnírez and Montero 1988). Rarnírez (1970) reponed tbat agaonids occasionally enter syconia of species otber tban tbeir usual host.